2008
DOI: 10.1590/s0006-87052008000200028
|View full text |Cite
|
Sign up to set email alerts
|

Teor de proteína e qualidade fisiológica de sementes de arroz

Abstract: RESUMOO trabalho teve como objetivo avaliar o teor de proteína como elemento auxiliar na determinação da qualidade fisiológica de sementes de arroz, além de correlacioná-la com a emergência em campo. Foram utilizados seis lotes de sementes de arroz, sendo três lotes da cultivar IRGA 417 e três lotes da cultivar IRGA 422 CL, submetidas ao conjunto de testes, para caracterizar o potencial fisiológico dos lotes: germinação, primeira contagem de germinação, envelhecimento acelerado, frio sem terra, comprimento de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
4
0
5
Order By: Relevance
“…The results for dry mass allowed for the separation of lots according to vigor levels, where lots 1 and 2 were the highest quality and lot 5 was the lowest, confirming the results found for the tests of field emergence, electrical conductivity and length of shoot. Bortolotto et al (2008) also observed that lots of two cultivars of rice seeds were able to be stratified using the dry mass test. Conversely, Braz and Rossetto (2009) observed that the dry mass test was not able to differentiate between five lots of sunflower seeds, however, lots were able to be differentiated in other tests, such as the field emergence test.…”
Section: Resultsmentioning
confidence: 91%
“…The results for dry mass allowed for the separation of lots according to vigor levels, where lots 1 and 2 were the highest quality and lot 5 was the lowest, confirming the results found for the tests of field emergence, electrical conductivity and length of shoot. Bortolotto et al (2008) also observed that lots of two cultivars of rice seeds were able to be stratified using the dry mass test. Conversely, Braz and Rossetto (2009) observed that the dry mass test was not able to differentiate between five lots of sunflower seeds, however, lots were able to be differentiated in other tests, such as the field emergence test.…”
Section: Resultsmentioning
confidence: 91%
“…According to Carvalho and Nakagawa (2012), because the first biochemical event known to occur upon exposure to unfavorable environmental conditions is a decrease in protein synthesis, seeds with higher physiological quality have higher protein content. Studying the relationship between protein content and physiological quality of rice seeds, Bortolotto et al (2008) observed that measurements of protein content can identify differences in quality between seed lots with different levels of physiological potential and can be correlated with seed emergence in the field. The authors further reported protein assessment as a promising finding for association with conventional tests.…”
Section: Resultsmentioning
confidence: 99%
“…Diferenças no vigor, associadas às características das sementes, são, geralmente, atribuídas à composição química, principalmente com relação à quantidade de reservas, ou à eficiência no metabolismo (Bortolotto et al 2008).…”
Section: Key-wordsunclassified
“…Lotes com maior qualidade fisiológica apresentam maior teor de proteína bruta, visto que o primeiro evento bioquímico verificado, quando as sementes são expostas a condições desfavoráveis de ambiente, é o dano à síntese de proteínas (Carvalho & Nakagawa 2000, Bortolotto et al 2008.…”
Section: Key-wordsunclassified